TRANSLANGUAGING - A TOOL FOR IGNITING ETHNIC SENSITIVITIES IN MULTI-ETHNIC SINDH, PAKISTAN - Ameer Ali; Maya Khemlani David; Syed Abdul Manan (Universitas Kuningan, 2021)
This study examines translanguaging as a political tool in Pakistan used to exploit ethnic sensitivities of speech communities. Building upon the grounded theory, concept of translanguaging was reconsidered to examine the politicized use of codes. The modified concept has been used to analyse the discourse of politicians and to demonstrate that such a mixed code has generated three tactical outcomes: politicization of language use, manipulation of general will, and exploitation of electoral support. The data comes from speeches of Pakistani politicians in Sindh, Pakistan between 2018 to 2020. This study demonstrates the politics of translanguaging, that is, the exploitation of language use for political purposes and argues that language policy experts should be made aware of such ramifications of the use of translanguaging as a political tool. Keywords: ethnic sensitivities; exploitation; language policy; Pakistan; Sindh; translanguaging.